Linkage between Institute and Industry - Raina, K. B.; Rathore, B. S.; Saini, J. S. (Journal of Engineering Education Transformations, 1992)
The educational reform of linking technical education with industry has been amongst the important educational innovations undertaken in this century. Linkage between institute and industry is now widely recognised as an essential requirement to train and develop the right kind of technical manpower necessary to sustain and promote industrial growth.